Формування системи сталого використання водних ресурсів у промисловому комплексі - Чередніченко, Ю.Г. (Економіка природокористування і сталий розвиток, 2019)
Досліджено передумови модернізації менеджменту водних ресурсів на виробничих підприємствах. Використовуючи глобальний підхід до регулювання процесу охорони вод від забруднення, розроблено систему сталого використання водних ресурсів у промисловому комплексі. Визначено її мету, завдання, принципи, об’єкти і суб’єкти регулювання використання водних ресурсів в індустріальному секторі та інструменти економіко-екологічного регулювання водоохоронної діяльності виробничих підприємств. The article discusses the prerequisites for modernization of water resources management at industrial enterprises, as the introduction of new principles of management dramatically changes the territorial organization of the industrial sector in Ukraine, resulting in changes in its consumption of water resources. Using a global approach, an industrial water management system has been developed that is fundamentally in line with the interests of enterprise administration, environmental authorities, and local communities and has minimal environmental impact. Its purpose, objectives and principles are defined. The objects of management in the system are all types of industrial water use, as well as the climatic peculiarities of the territory and the water management infrastructure used by production structures. The subjects of regulation of the use of water resources in the industrial complex are considered. Special attention is paid to the instruments of economic and environmental regulation of water protection activities of manufacturing enterprises. Among them are legal, financial and economic, administrative, information, technical and technological, innovation and investment. An important requirement for the system of planning, regulation and control over the use of water in the industrial sector of the Ukrainian economy is its flexibility, because its organizational structure must provide prompt response to changes, both external and internal environment, and be able to adapt quickly to them. Thus, the formation of an industrial water management system is a complex and multidimensional process that depends on the sustainable development of the entire economy of the state and the protection against threats and dangers posed by future climate change on the planet.